(untitled) (Ameghiniana, 2014)
Seven trilobite species are described from the Yongwol Group (Cambrian-Ordovician) of Korea: i.e., Micrognostus aff. elongatus (Chien), Micragnotus sp., Pseudorhuptagnostus (Machairagnostus) kentayensis (Ergaliev), Fatocephatus hunjiangensis Duan and An in Kuo el al., Koldinioidia longa Lu and Lin, Hysterolenus sp., and Anzasskiella? sp. All genera, except Micragnostus, are documented for the first time in Korea. The faunal assemblage consists predominantly of Fatocephalus constituting approxirnately 60% in abundance and is named as the Fatocephalus fauna. Agnostoid trilobites compose as much as 25% of the fauna, whereas other polymeroids are less commonly observed. The Fatocephalus fauna provides the first biostratigraphic reference point for the uppermost Cambrian interval of the Yongwol Group. Although Micragnostus, Koldinioídia and Hysterolenus are cosmopolitan in their distribution, the fauna as a whole shows interesting biogeographic links with North China, South China, Australia, Kazakhstan, and South America. The occurrence of fair arnounts of pandemic taxa in the present collection, coupled with little evidence of post-morten transportatíon, suggests that the Falocephalus fauna may have inhabited in a relatively quiet and deep-water environment.